Seasonal dynamics of nitrous oxide in sea ice of the Central Arctic: insights from the MOSAiC Expedition - Muller, Sofia; Abrahamsson, K; Angelopoulos, M; Bauch, D; Crabeck, Odile; Damm, Ellen; D'Angelo, A.; Fripiat, François; Nomura, Daïki; Van Hanja, J; Zhan, Liyang L.Z.; Delille, B. (2022)
info:eu-repo/semantics/nonPublished